Evaluation of Amide Proton Transfer-Weighted Imaging for Risk Factors in Stage I Endometrial Cancer: A Comparison With Diffusion-Weighted Imaging and Diffusion Kurtosis Imaging - Jin, Xingxing; Yan, Ruifang; Li, Zhong; Zhang, Gaiyun; Liu, Wenling; Wang, Hongxia; Zhang, Meng; Guo, Jinxia; Wang, Kaiyu; Han, Dongming (Frontiers in Oncology, 2022)
Background Endometrial cancer (EC) is one of the most common gynecologic malignancies in clinical practice. This study aimed to compare the value of diffusion-weighted imaging (DWI), diffusion kurtosis imaging (DKI), amide proton transfer-weighted imaging (APTWI) in the assessment of risk stratification factors such as histological subtype, grade, stage, and lymphovascular space invasion (LVSI)) in stage I EC. Methods A total of 72 patients with stage I EC underwent pelvic MRI. The apparent diffusion coefficient (ADC), mean diffusivity (MD), mean kurtosis (MK), and magnetization transfer ratio asymmetry (MTRasym(3.5 ppm)) were calculated and compared. Results MTRasym (3.5 ppm) and MK were greater and ADC and MD were lower in the non-adenocarcinoma, stage IB, IVSI-positive, high-grade, and non-low-risk groups than in the adenocarcinoma, stage IA, IVSI-negative, non-high-grade, and low-risk groups, respectively (all P < 0.05). MK and MTRasym (3.5 ppm) were moderately positively and ADC and MD were mildly negatively correlated with risk stratification, respectively (r = 0.640, 0.502, - 0.358, and -0.438). MTRasym (3.5 ppm), MD, and MK were independent predictors of risk stratification in stage I EC, and the combination of them had the strongest predictive value (AUC, 0.906; sensitivity, 70.97 %; specificity, 92.68 %). The validation model was consistent with the above results, and its ROC curve and calibration curve showed good accuracy (AUC, 0.917) and consistency. Conclusions APTWI has similar utility to DWI and DKI for non-invasive assessment of aggressive behavior in stage I EC, and the combination of MD, MK, and MTRasym (3.5 ppm) may serve as an imaging marker for evaluating risk stratification in stage I EC.